The Euratom PULSAR project - Simonini Alessia; Delannay Nicolas; Spindler Brieuc (EPJ Nuclear Sciences & Technologies)
PULSAR (PU-238-coupLed dynamic power system for SpAce exploRation and beyond) was a research and innovation project funded by the European Commission between 2022 and 2024. The aim of this project was to establish building blocks for the development of Radioisotope Power Systems (RPS) fueled by Pu-238 with European technologies and standards. Radioisotope Power Systems (RPS) is a key enabling technology for exploration of locations hidden from the sun for prolongated periods, or of deep space, where the sun cannot deliver sufficient power to spacecrafts. This project has brought together leading stakeholders in the field of space and nuclear. PULSAR consortium includes nine partners: Tractebel (coordinator), SCK CEN, CEA, JRC, Airbus DS, ArianeGroup, UBFC, INCOTEC and ARTTIC. The paper provides a presentation of the project, the organization of the different work packages between partners, the objectives and the achievements obtained. Future prospect and expected challenges are presented based on the hypothesis assumed in PULSAR.